Multifrequency dielectric sensing of moisture and sludge contamination in crude palm oil - Hamdan, Khairunnisa (2012)
Deterioration of Crude Palm Oil (CPO) quality caused by contamination during and after milling stages is a serious problem in palm oil processing. These include contamination pick-up during milling such as sterilizer condensate introduced during sterilizing stage and badly oxidized sludge oil during purification stage. Meanwhile, contamination after milling stages occured due to illegal activities such as siphoning off CPO while being transported from mill to refineries. The amount that was siphoned off was then replaced by liquid such as water, sludge, diesel or used oil which resulted in deterioration of the CPO being processed at the refineries. The conventional testing methods to measure CPO quality mostly depending on the determination of parameters such as iodine value (IV), peroxide value (PV),Deterioration of Bleacheability Index (DOBI), free fatty acid (FFA) and moisture content. The procedures to obtain these parameters are laborious, time consuming and require skilled operators. In-situ monitoring and early detection of CPO contamination could lessen oil degradation, thus enhance the value of the final palm oil products. Therefore, an efficient technique for CPO quality monitoring is needed to enhance the CPO quality and production process. This study used dielectric spectroscopy technique to detect possible contamination in homogeneous mixture of CPO. Initially, dielectric properties of pure CPO were determined. After that, the dielectric properties of CPO which were artificially contaminated with water and sludge were measured at different temperatures and contamination levels. For water contamination test, dielectric properties of CPO was measured using a 16452A Agilent liquid dielectric test fixture which was connected to a 4263B Agilent LCR meter over six frequencies, ranged from 100 Hz to 100 kHz. For sludge contamination test, the liquid dielectric test fixture was connected to a 4294A Agilent precision impedance analyzer ranging from 3 MHz to 30 MHz. Both tests were replicated three times with a randomized order of temperature and contaminant levels. The variations of dielectric properties of pure and homogeneous mixture of contaminated CPO at different temperature levels were observed and analyzed using ANOVA and Duncan’s multiple range test (DMRT). The principal component regression (PCR) and partial least squares (PLS) analysis were used to develop model for contamination prediction. The results showed that, there was generally significant different in the value of the mean measured dielectric constant as the temperature increased from 28°C to 55°C (p<0.0001). This study also found that when water was introduced into the CPO, the value of dielectric constant (measured at frequency ranged from 100Hz to 100 kHz) increased from 3.01 to 4.73 with increasing contamination levels. When sludge was introduced into the CPO, the value of dielectric constant (measured at frequency ranged from 3MHz to 30MHz) increased from 3.01 to 63.53 with increasing contamination levels. Generally for both test, there were significant differences between the dielectric constant of pure and contaminated CPO(p<0.0001). The PCR and PLS calibration models showed a good prediction capability for different temperature with sludge and water contamination levels. The classification of water contamination yielded very substantial correlation with r2 value ranged from 0.96 to 0.99. The best result was obtained at 55ºC with the lowest value of SECV of 0.58%. The classification of sludge contamination yielded very substantial correlation with r2 value ranged from 0.91 to 0.98. The best result was obtained at 28ºC with the lowest value of SECV of 1.04%. The result from this study could provide the foundation for studies on probing the physiochemical properties of CPO for in-situ monitoring of CPO quality. This study found that the frequency range substantial for contamination detection is generally low (<12 MHz). This is very attractive for industrial application because instrumentation required for such measurements is relatively inexpensive and does not have signal integrity issues associated with high frequency instrumentation.